2022
DOI: 10.1210/jendso/bvac004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Pheochromocytomas and Sympathetic Paragangliomas

Abstract: Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors arising from chromaffin cells of the adrenal medulla or extra-adrenal paraganglia, respectively. PPGLs have the highest degree of heritability among endocrine tumors. Currently, ~40% of PPGL individuals have a genetic germline and there exist at least 12 different genetic syndromes related to these tumors. Metastatic PPGLs are defined by the presence of distant metastases at sites where chromaffin cells are physiologically absent. Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 64 publications
0
12
0
18
Order By: Relevance
“…Pheochromocytoma would be diagnosed in the outpatient setting as the patients experience bursts of hypertension episodes associated with sweating, palpitations, and headache secondary to abrupt catecholamine release [ 11 ]. Nevertheless, and mainly through the high interindividual differences in catecholamines sensitivity, there is a poor correlation between the levels of circulating catecholamines and the symptomatic complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Pheochromocytoma would be diagnosed in the outpatient setting as the patients experience bursts of hypertension episodes associated with sweating, palpitations, and headache secondary to abrupt catecholamine release [ 11 ]. Nevertheless, and mainly through the high interindividual differences in catecholamines sensitivity, there is a poor correlation between the levels of circulating catecholamines and the symptomatic complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, sustained or paroxysmal hypertension is the most common sign of pheochromocytoma. 4 For instance, Philips 5 reported that paroxysmal hypertension and sustained hypertension occur in 45% and 50% of patients with pheochromocytoma, respectively, and only 5% of patients remain normotensive. In our case, frequent blood pressure measurements showed no evidence of paroxysmal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Paragangliome im Thorax/Abdomen können offen und endoskopisch reseziert werden. Postoperativ können Antihypertensiva schrittweise dosisreduziert und häufig beendet werden 4 , 46 , 50 , 52 , 53 .…”
Section: Paragangliom/phäochromozytom (Ppg/pcc)unclassified